Effects of combined shade and drought stress on turf‐type bermudagrasses. Issue 1 (29th April 2021) - Chhetri, Manoj; Fontanier, Charles; Moss, Justin Q.; Wu, Yanqi
Abstract: Shade and drought commonly occur together in turfgrass systems due to competition with trees for light and soil water. Two greenhouse studies were conducted to evaluate the effects of combined drought and shade stress on bermudagrass [ Cynodon dactylon (L.) Pers.] and hybrid bermudagrass [ C . dactylon (L.) Pers. × C . transvaalensis Burtt Davy] physiology. 'Latitude 36 Turf Bermudagrass' (Latitude 36 TM ) hybrid bermudagrass and 'Riley's Super Sport' (Celebration ® ) bermudagrass were selected for Experiment 1, while 'Patriot' hybrid bermudagrass was added as a shade‐sensitive cultivar in Experiment 2. Washed plugs of each cultivar were planted in growth tubes (10 cm diameter by 46 cm length polyvinyl chloride pipe with a flat bottom cap) filled with a 1:1 topsoil/sand root‐zone. Each experiment was conducted as a completely random design with two factors (cultivar and irrigation) repeated under two light environments. Light environment was defined as either adequate light (20.8–26.8 mol m –2 d –1 ) or low light (9.7–10.1 mol m –2 d –1 ) conditions. Irrigation was applied by hand to achieve either 100% (well‐watered) or 50% (drought) replacement of evapotranspiration (ET). Under drought conditions, low light resulted in a gradual decline in ET rate, whereas adequate light showed a sharp decline in ET rate over time. Under adequate light, Patriot consumed the most water among cultivars for either well‐watered or drought conditions. In contrast, Patriot (well‐watered) had the lowest water use in the low light environment, suggesting shade tolerance could potentially influence drought response under low light environments.